The connection between fine motor skills and speech development at the nursery age - Bulaja, Ana; Krajačić, Monika; Mustafić, Jelena (Rethinking childhood II: child and space, 2026)
Speech is the foundation of human communication, and it is important for the child’s overall development. The basis of speech development is formed during early childhood. The most intensive period for acquiring speech are the first three years of a child’s life in their family and kindergarten environment. A child has an innate predisposition for learning to speak. By using a system of signs and symbols, the child is able to communicate and express their knowledge, feelings, needs and thoughts to others. Children’s hands are constantly active from an early age, and children largely communicate with the world that surrounds them through their hands. The hand consists of the palm and fingers that enable the development of fine motor skills. Fine motor skills are a set of movements of bones, joints and muscles of the hand and fingers, the goal of which is to perform small and precise movements. The development of fine motor skills begins at birth, from the first movement of the hand. The areas in the brain responsible for finger movements and speech are located very close to each other, and they are connected. By encouraging the development of fine motor skills from an early age, one also encourages the development of the nearby brain areas that govern the development of speech. The level of child speech development is proportional to the degree of fine finger movement formation. The more active the child’s fingers are, the more advanced their speech, emotional, and intellectual development tend to be. Preschool and kindergarten teachers are the most important speech models for a child. One of the kindergarten teacher roles in the educational process is to create a stimulating speech environment that encourages speech development and speech skills. In this regard, planning development tasks is essential to support teachers in their educational work. These tasks include: the development of listening skills and understanding speech content, the development of the interpretation of experience through speech and language games, and acquisition of new words and vocabulary enrichment. Fine motor skills activities that can be used to facilitate and positively impact the development of speech in children from an early age are the following: art activities (painting, drawing, modelling, cutting, gluing, pasting, papier-mâché making), table-toy or manipulative activities (inserting, joining, stacking), stage-musical activities (dramatisation of stories, various speech-language games), and initial reading activities (listening, reading, retelling, describing stories). Educators working directly with children point out that various fine motor activities have an impact on the increase of interactions between children, as well as on the development of their expression and creativity within the educational group. The combination—of kindergarten teachers as speech models, a stimulating spatial and material environment, and the contents with which the child is surrounded—significantly affects the proper development of a child’s speech, their development of fine motor skills, and the development of all competencies that remain intertwined and complementary, collectively building the complete personality of each child as an individual.